2021
DOI: 10.3389/fonc.2021.687010
|View full text |Cite
|
Sign up to set email alerts
|

Transvesical Retzius-Sparing Versus Standard Robot-Assisted Radical Prostatectomy: A Retrospective Propensity Score-Adjusted Analysis

Abstract: ObjectivesTo estimate the safety and efficiency of transvesical Retzius-sparing robot-assisted radical prostatectomy (T-RARP) compared with standard robot-assisted radical prostatectomy (S-RARP) for localized prostate cancer (PCa).Materials and Methods174 patients bearing localized PCa and undergoing T-RARP or S-RARP between October 2017 and January 2020 were retrospectively enrolled in our analysis. All potential baseline confounders were strictly restrained with propensity-score matching (PM) method (1: 1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Based on our results, both the transvesical and posterior approaches are superior over the anterior approach concerning postoperative early return to UC, which could be attributed to the common advantage of these two Retzius-sparing surgeries. Both the transvesical and posterior techniques allowed the prostate gland to be removed without disrupting the integrity of Retzius space, thus providing a strong rationale for achieving enhanced UC recovery after RARP [ 9 , 11 ]. All UC-related structures in the Retzius space, such as the endopelvic fascia, puboprostatic ligaments, and detrusor apron, were preserved to provide a strong supportive mechanism and stabilize the urethra [ 2 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our results, both the transvesical and posterior approaches are superior over the anterior approach concerning postoperative early return to UC, which could be attributed to the common advantage of these two Retzius-sparing surgeries. Both the transvesical and posterior techniques allowed the prostate gland to be removed without disrupting the integrity of Retzius space, thus providing a strong rationale for achieving enhanced UC recovery after RARP [ 9 , 11 ]. All UC-related structures in the Retzius space, such as the endopelvic fascia, puboprostatic ligaments, and detrusor apron, were preserved to provide a strong supportive mechanism and stabilize the urethra [ 2 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anterior approach was done following the modified technique proposed by Menon et al [ 12 ], while the posterior approach was carried out as described by Galfano et al [ 8 ]. As presented in our published studies [ 9 11 ], the detailed surgical steps of the transvesical approach to RARP are shown in Figure 1 . Anatomically extended pelvic lymph node dissection (ePLND) was conventionally executed on condition that the preoperative estimated risk in lymph node metastasis exceeded 5%, while the performance of ePLND was routinely abandoned in patients with a lower risk of nodal involvement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative follow-up was regularly arranged every 3 months within the first year after surgery and every 6 months from the second year after surgery for each patient. Each case routinely underwent postoperative PSA tests every 3 months to monitor the biochemical recurrence (BCR), which was considered as the occurrence that two consecutive rising serum PSA values measured on two separate occasions were 0.2 ng/mL or greater after prostatectomy [ 2 , 25 ]. BCR-free survival was regarded as the interval length from the date of surgery to that of BCR.…”
Section: Methodsmentioning
confidence: 99%
“…BCR-free survival was regarded as the interval length from the date of surgery to that of BCR. Urinary continence (UC) was considered as no use of pads or use of a single safety pad within 24 hours [ 2 , 25 ]. A safety pad was defined as “no involuntary loss of urine, but a pad was still used.” In the meantime, urinary incontinence was defined as the use of > one pad within 24 hours.…”
Section: Methodsmentioning
confidence: 99%